TRANSFORMASI DIGITAL MARKETING DAN E-WOM: ANALISIS PENGARUHNYA TERHADAP MINAT BELI KONSUMEN DALAM ERA EKONOMI DIGITAL - Iwan Setiawan; Pindo Asti (CV. Denasya Smart Publisher, 2025)
This study aims to systematically review the influence of digital marketing and electronic word of mouth (E-WOM) on consumer purchase intention. Using a systematic literature review (SLR) approach, five peer-reviewed journal articles published between 2022 and 2023 were analyzed, focusing on digital consumer behavior in the context of social media platforms such as TikTok and Instagram, as well as e-commerce. The review identifies that digital marketing strategies—particularly content marketing and social media engagement—positively affect purchase intention, especially when mediated by consumer trust and brand awareness. Similarly, E-WOM, delivered through influencers, customer reviews, and celebrity endorsements, is found to significantly shape brand image and influence purchase decisions. The findings also highlight that the effectiveness of digital marketing and E-WOM varies depending on platform type, message form, and product category. This study contributes to a deeper understanding of consumer response patterns in digital environments and offers practical implications for marketers to optimize engagement strategies. Recommendations for future research are also presented to address the current limitations and explore emerging trends in digital consumer behavior.